Spanish Transcultural Adaptation and Validity of the Behavioral Inattention Test - Ángel Sánchez-Cabeza; Elisabet Huertas-Hoyas; Nuria Máximo-Bocanegra; Rosa María Martínez-Piédrola; Marta Pérez-de-Heredia-Torres; Jorge Alegre-Ayala (Occupational Therapy International)
Objective. To adapt, validate, and translate the Behavioral Inattention Test as an assessment tool for Spanish individuals with unilateral spatial neglect. Design. A cross-sectional descriptive study. Setting. University laboratories. Participants. A sample of 75 Spanish stroke patients and 18 healthy control subjects. Interventions. Not applicable. Main Outcome Measures. The Behavioral Inattention Test. Results. The Spanish version of the Behavioral Inattention Test shows a high degree of reliability both in the complete test (α = .90) and in the conventional (α = .93) and behavioral subtests (α = .75). The concurrent validity between the total conventional and behavioral scores was high (r=-.80; p<0.001). Significant differences were found between patients with and without unilateral spatial neglect (p<0.001). In the comparison between right and left damaged sides, differences were found in all items, except for article reading (p=0.156) and card sorting (p=0.117). Conclusions. This measure is a useful tool for evaluating unilateral spatial neglect as it provides information on everyday problems. The BIT discriminates between stroke patients with and without unilateral spatial neglect. This measure constitutes a reliable tool for the diagnosis, planning, performance, and design of specific treatment programs intended to improve the functionality and quality of life of people with unilateral spatial neglect.